"Shopping while Black": Black consumers' management of racial stigma and racial profiling in retail settings. (February 2020) - Pittman, Cassi
This article draws on qualitative interview data collected from 55 African Americans residing in the New York City area to examine African Americans' experiences of consumer racial profiling or "Shopping While Black." I find that racial discrimination alters African Americans' experiences as consumers. Racial stigma in retail settings impacts the consumptive process for Blacks in two central ways. First, retail settings are often sites where anti-Black bias is made evident, requiring Black shoppers to navigate racial hierarchies while procuring goods. Second, discrimination alters the experience of shopping, arguably raising the costs and reducing the rewards derived from consumption. When a store's sales staff is hesitant to serve Black shoppers or suspects that they are prospective shoplifters, shopping no longer becomes a form of leisure. A qualitative assessment of Blacks' reports of racial stigma and discrimination in retail settings reveals that race can change the meaning and status attached to goods, when they are sought out or owned by racial minorities. By examining Blacks' experiences of retail racism and the cultural strategies they adopt in responding to occasions when they are treated discriminatorily, this research brings to light Blacks' experiences of discrimination on the ground, while also examining how racism impacts the quality of Black consumers' experiences.